THE EFFECTIVENESS OF AROMATHERAPY ABDOMINAL MASSAGE TECHNIQUE EFFLURAGE COMPARED WITH ABDOMINAL STRETCHING EXERCISE TO REDUCE PRIMARY DYSMENORRHEA IN TEENAGE GIRLS JUNIOR HIGH SCHOOL IN DENPASAR - Antari, Dewa Ayu Chintya; Winaya, I Made Niko; Wiryanthini, Ida Ayu Dewi (Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACT Primary dysmenorrhea is cramping in lower abdomen, back pain,often with diarrhea and nausea, and unstable emotions and often occur in age 13-15 years and happen in time 24-48 hours. It will affect functional activity teenage girls that needed treatment to reduce the pain. The purpose of this study was to determine the differences in the effectiveness of aromatherapy abdominal massage technique efflurage with abdominal stretching exercise in reducing pain of primary dysmenorrhea in teenage girls at junior high school in Denpasar. Measurement of pain using Numerical Rating Scale (NRS). This research is an experiment research design with pretest and posttest group design. The study involved 20 samples then divided into 2 group. Group 1 aromatherapy abdominal massage technique efflurage and group 2 abdominal stretching exercise. Range of pain in group 1 decrease of 2,00 and group 2 decrease of 3,50. Paired T-test result in group 1 is p=0,000 and group 2 is p=0,000. The difference between group 1 and group 2 was obtained p=0,001. It was concluded that abdominal stretching exercise more effective to reduce the pain of primary dysmenorrhea in teenage girls junior high school in Denpasar compared with aromatherapy abdominal massage technique efflurage. Keywords : Primary dysmenorrhea, Aromatherapy Abdominal Massage Technique Efflurage, Abdominal Stretching Exercise, Numerical Rating Scale (NRS)